Explaining Torture: A Case Study - Cottam, Martha (2018)
During the late 1960s and early 1970s, most Latin American countries experienced military coups and military interventions in government affairs. One of the worst consequences of these military interventions was the torture and murder of thousands of people. This study focuses on the perpetrators of torture and examines group influences on the occurrence of torture and the behavior of torturers. To achieve this goal, we have conducted field research to interview and evaluate individuals who were members of the Chilean police and military during the 1980s. Interviews were conducted with Chilean military and police torturers active during the military regime (1973 – 1990). Group influences are strongly associated with the institutional context. The study identifies common patterns among the perpetrators but also considers the marked differences between them and demonstrates the important role of the group in enabling the perpetration of torture. Few studies have examined torture behavior in an institutional framework, and the identification of these features may allow this type of crime to be prevented